DEVELOPMENT OF AN INSTRUMENT TO MEASURE CONCEPTUAL MASTERY OF GLOBAL WARMING FOR MIDDLE SCHOOL STUDENTS - Fadillah, Rofi Wafa; Rusyati, Lilit; Rochintaniawati, Diana; Agustin, Rika Rafikah (Universitas Tanjungpura, 2025)
This study develops and validates an assessment tool to measure middle school students' understanding of global warming. The instrument includes 21 multiple-choice questions covering key concepts like the greenhouse effect climate change and mitigation strategies. After expert validation and pilot testing with 63 students, the tool demonstrated high reliability (Cronbach's alpha = 0.71). The validation process revealed that while most items effectively assessed various aspects of conceptual mastery, some items failed to meet the validity criteria due to issues such as ambiguous phrasing, inappropriate cognitive difficulty for the target grade, and potential confusion in question structure. Despite these challenges, the instrument shows promise as a reliable tool for evaluating students